Towards peer-to-peer content indexing - Baquero, Carlos (2003)
Distributed Hash Tables are the core technology on a significant share of system designs for Peer-to-Peer information sharing. Typically, a location mechanism is provided and object identifiers act as keys in the index of object locations. When introducing a search mechanism, where single words are used as keys, the key image cardinality will be driven by the word popularity and most of the present designs will be unable to load balance the index among the nodes. We present two contributions: A design that allows participating nodes to load balance the indexing of popular keys and avoid content hot-spots on single nodes; A distributed mechanism for probabilistic filtering of popular keys (with low search relevance) that paves the way for scalable full content indexing.